The need for lifelong learning. (2018) - Christie, Luke Gerard; Kumar, Gajendra
The more we learn and acquire knowledge, the more empowered and better would our life become. In more than one scenario, people who upgraded themselves or were more knowledgeable came off as being resilient, innovative with the attitude of being socially and emotionally resilient. The more learning becomes part of our daily life and curious we are, life becomes more gratifying and energetic for achieving one's dreams and goals. Acquisition of more knowledge helps in solving problems effectively with an efficient and innovative bent of mind. The desire to make learning a life-long activity and a continuous process helps create value and add value to what we do or in living life to the fullest and in reaching out to others with integrity and in principle. Life has to be lived not as a monotonous activity but has to be experienced from within and learning creates that path.